The EU, the UN and Collective Security : Making multilateralism effective - Krause, Joachim (Contemporary security studies., 2012)
This book examines the effectiveness of multilateralism in ensuring collective security and, in particular, the EU's role in this process. In 1992, shortly after the end of the Cold War, a Security Council Summit in New York reaffirmed the salience of the system of collective security and stated the determination of the Heads of State to maintain it as the prime international instrument for preserving peace. Twenty years later, however, the record of collective security as well as of multilateralism has not been very encouraging.